The Effect of ESG, Human Capital, and Green Innovation Disclosure on Financial Performance - Yeny Widya Tuti; Tantina Haryati; Nanda Wahyu Indah Kirana (Universitas KH. Abdul Chalim Mojokerto, 2025)
Financial performance is a crucial element for a company's sustainability because it determines its ability to make a profit. However, companies that are members of the SRI-KEHATI index experienced fluctuations in performance based on ROA during 2019–2023. This study focuses on companies in the SRI-KEHATI index listed on the IDX during the period, to empirically examine the influence of ESG, human capital, green process innovation, and green product innovation on financial performance. The analysis used secondary data from financial, annual, and sustainability reports as many as 125 observations were obtained through purposive sampling. This study uses a quantitative approach and SEM-PLS analysis techniques, which results in findings that ESG, human capital, and green process innovation have a positive and significant impact on financial performance, while green product innovation has a non-significant negative influence.